Analysis of Psychological Trends and Policy Recommendations of Medical Staff in Northern China in the Latter Stages of the COVID-19 Pandemic - Yang, Xueping; Miao, Junxiao; Fan, Weizhong; Wang, Lili; Sun, Shuning; Li, Hongshi; Wang, Na; Wang, Xuesong; Lin, Muhui; He, Ru (Frontiers in Psychology, 2021)
Aim: Since the 2019 coronavirus disease (COVID-19) outbreak, medical staff have faced greater psychological stress and are prone to psychological problems such as anxiety and depression, as confirmed by several studies. This study further clarifies the psychological status of Chinese medical staff during the stable phase of the pandemic through a cross-sectional investigation in a large population sample in northern China. Methods: Subjects: Clinical frontline medical staff from seven hospitals in Liaoning Province were recruited from November 2020 to February 2021. Research tools: The research tools used were the Self-Rating Anxiety Scale (SAS), Self-Rating Depression Scale (SDS), Simplified Coping Style Questionnaire (SCSQ), and General Status Questionnaire. Statistical Analysis: SPSS 22.0, ANOVA variance analysis, and multiple logistics regression were used for statistical analysis. P-values of <0.05 indicated significant statistical differences. Results: A total of 3,144 medical staff completed the survey (599 men [19.1%] and 2,545 women [80.9%]; 1,020 doctors [32.4%] and 2,124 nurses [67.6%]). Among all subjects, the rates of anxiety and depression were 21.1% (663/3,144) and 43.9% (1,381/3,144), respectively. Multiple logistic comparative analysis revealed that age (OR = 1.272, 95% CI = 1.036–1.561, P = 0.022), the need for psychological counseling (OR = 1.566, 95% CI = 1.339–1.830, P < 0.001), and the coexistence of depression (OR = 0.050, 95% CI = 0.038–0.066, P < 0.001) were significantly associated with anxiety. Coexisting anxiety was also associated with the occurrence of depression (OR = 0.050, 95% CI = 0.038–0.065, P < 0.001). Conclusions: In the later stages of the pandemic in China, the occurrence rates of anxiety and depression among medical staff remain high. In addition to age, there is little correlation between anxiety or depression and general factors such as gender and profession.